2011
DOI: 10.1007/s00705-011-1066-0
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a replicon and an infectious cDNA clone of the Sofjin strain of the Far-Eastern subtype of tick-borne encephalitis virus

Abstract: Tick-borne encephalitis virus (TBEV) causes severe encephalitis in humans. The Sofjin-HO strain is the prototype strain of the TBEV far-eastern subtype, and is highly pathogenic in a mouse model. In this study, we constructed replicons and infectious cDNA clones of the Sofjin-HO strain. The replication of the replicon RNA was confirmed, and infectious viruses were recovered from the infectious cDNA clone. The recombinant viruses showed similar virulence characteristics to those of the parental virus. While cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…These mutations increase viral interaction with negatively charged GAGs allowing for more efficient infection. While GAG-binding variants may have a replicative advantage in cell lines, many of these have been shown to be attenuated for neuroinvasiveness in vivo [ 13 , 28 , 29 , 30 , 31 ]. Interaction of viral proteins with GAGs may serve to concentrate virus on the cell surface and thus facilitate interaction with high affinity receptors [ 13 ]—such as D-SIGN, TIM, and TAM—which were recently implicated in MBFV entry [ 32 ] but have yet to be studied in TBFVs.…”
Section: Effects Of Viral Proteins On Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…These mutations increase viral interaction with negatively charged GAGs allowing for more efficient infection. While GAG-binding variants may have a replicative advantage in cell lines, many of these have been shown to be attenuated for neuroinvasiveness in vivo [ 13 , 28 , 29 , 30 , 31 ]. Interaction of viral proteins with GAGs may serve to concentrate virus on the cell surface and thus facilitate interaction with high affinity receptors [ 13 ]—such as D-SIGN, TIM, and TAM—which were recently implicated in MBFV entry [ 32 ] but have yet to be studied in TBFVs.…”
Section: Effects Of Viral Proteins On Virulencementioning
confidence: 99%
“…However, mutations in domain II dominate, as it is an extended structure that forms a large portion of the surface of the protein. One attenuating mutation in domain II of TBEV, E122G, has arisen several times in various laboratory settings, including cell passage, neutralizing antibody escape mutants, and infectious cDNA recovery, as well as being identified in low virulence natural isolates [ 28 , 29 , 30 , 31 , 34 ]. In one study that evaluated the mutation in greater detail, the researchers found that the attenuated TBEV E122G mutant displayed a more pronounced increase in binding affinity to BHK-21 cells than did an attenuated E201K mutant compared to the wild type virus [ 28 ].…”
Section: Effects Of Viral Proteins On Virulencementioning
confidence: 99%
“…These findings provide a foundation for further 36 research to identify the pathogenic mechanisms of TBEV. The virulence of the recombinant viruses was compared with those of the parental 95 infectious cDNA clones, Oshima-IC-pt and Sofjin-IC-pt (Takano et al, 2011). 96…”
mentioning
confidence: 99%
“…This is consistent with previous data for WNV [18], and may be related to the low incidence rate in flavivirus-infected individuals. Our previous data showed that peripheral viral multiplication did not differ between the Sofjin-HO and Oshima 5-10 strains in B6 mice and did not correlate with the progression of disease in TBEV infection [10,29]. Considering the results of intracerebral infection in B6.MSM-Oas mice, it may be possible to distinguish clinical conditions based on the TBEV strain after viral invasion into the brain.…”
Section: Discussionmentioning
confidence: 99%